I will give them an everlasting name : pastoral care for Christ's converts from Islam - Miller, Duane Alexander (Regnum practitioner series., 2020)
"What are the challenges faced by Christ's converts from Islam, and how can their Christian friends help them to overcome those challenges? In this book, Duane Miller draws on years of pastoral experience and academic research to propose practical resources and ideas that have proved successful in the past. This book is not a work of clinical counseling, but a resource ready to be read and applied by the experienced pastor as much as someone who is new to ministry among Muslim-background seekers and converts from Islam. Addressing topics from church history to baptism, and from finances to prayer, the book is being published at a time when the global Church is seeing unprecedented numbers of new disciples coming from Muslim backgrounds, and was written to help the Church in providing them with a new and welcoming home."--Publisher.